The impact of sensory simulations on young children’s science learning (International Conference on Computers in Education, 2019)
Simulation was found to be an effective tool for learners to learn science. However, young children might have difficulty to integrate their understanding and the simulation because of inability to process virtual and abstract information. This study proposed a sensory simulation which helps young children learn science. The results show that the sensory simulation help the young children assimilation the concept and reflect in some questions while it did not enhance learning in other questions. More qualitative interview data should be collected to understand the cognitive process of using sensory simulation.